Directions of functions and missions distribution between the National Guard of Ukraine and the National Police of Ukraine in the field of public order and public safety - Lavnichenko, О. V.; Hodlevsyi, S. О.; Garmash, V. P. (Honor and Law, 2019)
The directions of the distribution of functions and tasks between the National Guard of Ukraine and the National Police of Ukraine in the field of public order protection and public safety are substantiated based on the current normative-legal framework, problem issues regarding the experience of law enforcement tasks being carried out by both domestic and foreign law enforcement agencies and certain principles , on which it is proposed to carry out such a division, as well as a number of suggestions and recommendations